PENGARUH REPUTASI PERUSAHAAN, DESKRIPSI PEKERJAAN, DAN KOMPENSASI YANG DITAWARKAN PERUSAHAAN TERHADAP MINAT MELAMAR PEKERJAAN - Sumardana, Octavianus; Ganesha Rahyuda, Agoes; Ketut Sintaasih, Desak (Buletin Studi Ekonomi, 2016)
The Effect Of Company’s Reputation, Job Description and Offered Compensation on Individual’s Intention to Apply a Job. Recruitment process is one of key HR activities that should be conducted appropriately in a company. However, the role of prospective employees in providing inputs to the company regarding the recruitment process is not clear. The aim of this research is to understand the perspectives of potential employees regarding the effect of company’s reputation, job description and offered compensation on individual’s intention to apply a job. The participants are 73 final-year undergraduate students at the Faculty of Economics and Business Universitas Udayana, with the proportionate stratified random sampling as the sampling method. This research used multiple regressions as its data analysis method. This research found that all three variables influence individual to apply a certain job. One interesting finding is that the individual tends to be motivated to apply job if he or she finds that the company has a clear job description   Keywords: company’s reputation, job description, offered compensation, intention to apply jobs
Keywords: company’s reputation, job description, offered compensation, intention to apply jobs